El proceso de valoración de intangibles a partir del método del costo : un caso de estudio para el Know How (2015)
ABSTARCT: One of the greatest challenges, at the start of the 21st century, is to quantify assets in transfer of knowledge processes generating a value in organizations; therefore it is important to recognize different valuation of intangibles proposals that are having a positive impact in enterprises competitiveness and sustainability. This being so, the main objective of this study is to identify the primary methodologies of valuation of intangibles assets and applying a Know How valuation methodology. To this end, a blend between documentary research and cost method was used as a methodological resource. It is obtained in the results that referring to valuation of intangibles, the most used methods in the academic and corporate field are as follows: cost, market and revenue value, being the cost method the ideal when quantifying this kind of intangible assets affecting an organization.